1971
DOI: 10.1071/ar9710671
|View full text |Cite
|
Sign up to set email alerts
|

Nychthemeral patterns of thermoregulation in high-yielding dairy cows in a hot dry near-natural climate

Abstract: The thermoregulatory responses of Israeli Holstein cows (33 kg milk/day) were determined during 4 days at 3-hr intervals in summer and in winter in their normal environment. The mean ambient conditions in summer and winter were 31.8 and 16.8�C black globe temperature, 32 and 43 % relative humidity, and 1.6 and 1.2 mlsec wind velocity respectively. Seasonal changes in cows from winter to summer were: 0. 11�C increase in tympanic membrane temperature, 0.37 and 2.6�C increments in rectal and mean trunk skin tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 0 publications
4
15
0
Order By: Relevance
“…The diurnal variation in respiratory rates and rectal temperatures agrees with the findings of BERMAN (3). Similar changes in body temperatures have also been observed in cattle (11,2,4), sheep and goats (9) and pigs (13) and have been related to proportional increases in reactions associated with heat dissipation. The close relationship between the diurnal changes in the respiratory rates and the physiologically effective temperatures agrees with the findings of STEINBACH (13).…”
Section: Discussionsupporting
confidence: 87%
“…The diurnal variation in respiratory rates and rectal temperatures agrees with the findings of BERMAN (3). Similar changes in body temperatures have also been observed in cattle (11,2,4), sheep and goats (9) and pigs (13) and have been related to proportional increases in reactions associated with heat dissipation. The close relationship between the diurnal changes in the respiratory rates and the physiologically effective temperatures agrees with the findings of STEINBACH (13).…”
Section: Discussionsupporting
confidence: 87%
“…The EVAP treatment appeared to maintain RT of the crossbred cows close to that of non-heat stressed purebred lactating cows (Trout et al 1998) but the RR value was slightly higher than that found by Trout et al (1998), suggesting that heat stress was not eliminated completely by the evaporative cooling system as a rise in RR precedes a rise in RT on exposure to rising ambient temperature (Berman and Morag 1971;Brown-Brandl et al 2003).…”
Section: Resultsmentioning
confidence: 48%
“…It has been widely reported that seasonal changes in ambient temperature can affect the body temperature rhythm in cows. For example, the mean body temperature and the amplitude of the body temperature rhythm are higher in the summer than in spring or winter (Berman, 1968;Berman and Morag, 1971). Body temperature is also affected by physiological state as the body temperature of lactating cows appears to be more influenced by elevated ambient temperature than non-lactating pregnant cows (Lefcourt and Schmidtmann, 1989).…”
Section: Introductionmentioning
confidence: 97%